Proses Penerimaan Diri Wanita Penyintas Bipolar di Yogyakarta - Aprilia, Eka; Andhita Dyorita Khoiryasdien (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Bipolar survivors often face extreme mood swings, where ODB (people with bipolar) will experience a mania phase characterized by increased energy and activity, and the opposite depressive phase, which causes decreased energy and the emergence of depressive symptoms. This condition is certainly a challenge for providers in carrying out daily activities. Self-acceptance is an important key for ODB to get through critical periods and kontrol emotional stability in order to achieve a more optimal quality of life. This study aims to explore the dynamics of the self-acceptance process in women with bipolar type 1 who have been diagnosed since 2013. This study uses a qualitative method with a case study approach to explore more deeply the subject's experience related to the self-acceptance process. Data were collected through in-depth interviews with a housewife who has two children and has lived with bipolar for more than 10 years. Despite facing major challenges, the subject managed to empower herself. The results of the study showed that self-acceptance in bipolar disorder is a complex process. The results showed that the subject had gone through five stages of self-acceptance according to the Kübler-Ross & Kessler model, namely denial, anger, bargaining, depression, and finally acceptance. In addition, the results of the study showed that supporting factors in this process include support systems, both social and emotional support from the family, as well as psychotherapy assistance that helps subjects identify problems more objectively.